Scaling ethics up and down: moral craft in clinical genetics and in global health research - Parker, Michael (J Med Ethics, 2015)
This paper engages with the question of what it is to ‘do good medical ethics’ in two ways. It begins with an exploration of what it might mean to say that health professionals practise good medical ethics as part of practising good ethical medicine. Using the example of the Genethics Club, a well-established national ethics forum for genetics professionals in the UK, the paper develops an account of moral craftsmanship grounded in the concepts of shared moral commitments and practices, moral work, ethics and living morality. In the light of this discussion, the paper goes on to consider what it might mean for a specialist in medical ethics, a bioethicist, to do good medical ethics. Finally, a research agenda focusing on the challenges of thinking about good medical ethics in a global context and a proposal for an innovative approach to bioethics methodology is outlined.